The Function of Natural Science in Lecturer Performance at Measurement at IAIN Curup - Bengkulu - Ratih Komala Dewi; Citra Puspa Permata (Postgraduate, University of Mataram, 2025)
The use of digital technology for lecturer performance management at IAIN Curup is elementary. Natural sciences—particularly psychology —can be applied to better understand human behavior, cognitive processes, stress responses, and other factors influencing workplace dynamics and employee well-being. In other aspects, to measure the performance of lecturers, in principle, it is reflected in the productivity in carrying out education and teaching, research, and community service, known as the Tri Dharma of Higher Education. It aims to formulate theories and laws that explain the natural world and predict future outcomes. The emergence of college management has transformed the landscape of Human Resource Management (HRM) by introducing advanced technologies, including artificial intelligence (AI), machine learning, and big data analytics. These innovations have enhanced HRM processes such as recruitment, training, performance evaluation, and employee engagement. This research is expected to provide information that natural and computer sciences play a role in managing the performance of lecturers at Institut Agama Islam Negeri Curup. Natural sciences play a critical role in understanding the dynamics of these technological advancements, offering insights into human behavior, cognitive processes, and organizational ecosystems. This article explores how principles of natural science integrate with modern HRM practices in university. Through a qualitative approach, we examine case studies to illustrate the application of natural science in human resources strategies at university, highlighting the advantages and challenges of adopting a scientifically-informed HRM framework.